COMPREHENSIVE MIDWIFERY CARE FOR SLEEP DISTURBANCES IN A MULTIGRAVIDA PATIENT : - Rostiana, Vina; Oktri, Yosi (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2024)
In the third trimester, women usually experience discomfort such as low back pain, frequent urination, fetal movements, heartburn, leg cramps, fatigue, especially sleep disturbances or difficulty sleeping until the morning. Third trimester pregnant women often experience sleep disturbances, this causes a decrease in sleep duration in pregnant women. Based on the Ministry of Health of the Republic of Indonesia, in 2021, the number of pregnant women in Indonesia who experienced sleep disorders reached 64%. This study aims to determine midwifery care to overcome sleep disorders in pregnant women. The method in this research is a case study approach. Data collection in this research used interviews and observation. The subject of this research was Mrs "U" G4P1A2 38 weeks pregnant with complaints of discomfort and sleep disturbances. The causes of sleep disorders in Mrs "U" were an enlarged uterus, increased fetal weight, shortness of breath, restlessness, difficulty falling asleep and frequently waking up at night because she wanted to urinate. The research results showed that after intervention through the use of video 6 times in more than 1 week with a duration of ± 10 minutes, Mrs. “U” decreased and felt better, felt more relaxed, slept more comfortably, and woke up less frequently at night. It can be concluded that the case study of comprehensive midwifery care for Mrs. “U” runs normally and is effective in overcoming the discomfort experienced. The result of this study being limited to a single patient, restricts the generalizability of the findings.Future research with a larger sample size is needed to validate these results and explore the broader applicability of this midwifery intervention. Keywords: Sleep Disturbances, Yoga Prenatal, Midwifery Care